Tdap vaccine and pregnancy. Why is itimportant? Safety and efficacy of thevaccine - Namizato Ikemiyashiro, Claudia Sofia (2025)
Pertussis (Bordetella pertussis) is a highly contagious respiratory disease that poses a significant threat to infants under six months of age, in whom clinical manifestations may be atypical and complications severe or fatal, including apnea, pneumonia, encephalopathy, and death. Despite the availability of effective vaccines for decades, pertussis continues to be a public health problem, with recurring epidemic cycles.Since the childhood vaccination schedule is not completed until six months of age, newborns and infants remain vulnerable. Tdap vaccination during pregnancy has been shown to be an effective and safe strategy for preventing the disease at this stage. Administering the vaccine between 20 and 36 weeks of gestation—preferably at least two weeks before delivery—ensures adequate transplacental transfer of antibodies, conferring passive protection to the newborn. Numerous observationalstudies and meta-analyses have shown significant reductions in hospitalizations, severe illness, and mortality in infants born to vaccinated mothers. Likewise, no significant maternal, obstetric, or neonatal risks have been observed. Nor has maternal vaccination been shown to clinically interfere with the infant's immune response after receiving their own vaccination schedule. Vaccination coverage among pregnant women in Peru is still suboptimal, highlighting the need for health personnel to commit to recommending and implementing this intervention in every pregnancy as an integral part of prenatal care.